1996
DOI: 10.1007/bf02560148
|View full text |Cite
|
Sign up to set email alerts
|

Selective arterial embolization of idiopathic priapism

Abstract: We report a case of idiopathic priapism that was only identified as high-flow or arterial priapism after drainage of the corpora cavernosa. Following failure of conservative and surgical treatment attempts, two consecutive embolizations of a unilateral penile artery were performed with gelgoam particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Given that blood gas analysis confirmed high‐flow priapism prior to creation of a surgical corporoglanular shunt, it is unlikely to represent a surgical complication. Other authors have theorized that ischaemic necrosis of the penile vasculature during prolonged ischaemic priapism may convert it to the high‐flow variety, which would explain the hypertrophy of common penile arteries and early arterial cavernosal blush/shunting in this case …”
Section: Matched Radial and Cavernosal Blood Gas Analysis Revealed Simentioning
confidence: 75%
See 1 more Smart Citation
“…Given that blood gas analysis confirmed high‐flow priapism prior to creation of a surgical corporoglanular shunt, it is unlikely to represent a surgical complication. Other authors have theorized that ischaemic necrosis of the penile vasculature during prolonged ischaemic priapism may convert it to the high‐flow variety, which would explain the hypertrophy of common penile arteries and early arterial cavernosal blush/shunting in this case …”
Section: Matched Radial and Cavernosal Blood Gas Analysis Revealed Simentioning
confidence: 75%
“…There are very few cases of non‐traumatic high‐flow priapism reported in the literature . Previous authors have reported cases of high‐flow priapism following shunting procedures for ischaemic priapism; however, these typically have an angiographic lesion at the site of the surgical shunt .…”
Section: Matched Radial and Cavernosal Blood Gas Analysis Revealed Simentioning
confidence: 76%
“…Mourikis/Chatziioannou/Konstantinidis/ Panourgias/Antoniou/Vlachos tologous blood clot was the embologenic agent of choice in the majority of these patients [1,[3][4][5][6][7][8][9][10][11][12]. Gelfoam particles or slurry was used in some patients for temporary occlusion [5][6][7] while n-butyl-cyanoacrylate has been injected in 3 men [8].…”
Section: Discussionmentioning
confidence: 99%
“…In our case the priapism was not due to a 'high-flow' state since an arteriosinusoidal fistula was not recognized on Doppler or arteriography. At least 36 patients with arteriosinusoidal fistula, almost exclusively secondary to local trauma, have been treated with selective embolization and a cumulative success rate of greater than 90% [3][4][5][6][7][8][9][10][11]. Au-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation